STUDI PERENCANAAN PENERANGAN JALAN UMUM TENAGA SURYA SISTEM TERPUSAT UNTUK JALAN BINUANG,NGARAI SIANOK,KABUPATEN AGAM SUMATERA BARAT - Hidayat, Taufik; Yulisman, Yulisman; Kamil, Mahyessie (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
PJU-TS(Solar Powered Lighting) is public street lighting where the electrical power for the lights is supplied by an independent system obtained from solar energy. This design aims to describe the PJU-TS design based on solar power and LEDs, with the durability of solar panel and LED modules without being connected to the electric power network and the lighting specifications used in the PJU-TS design at the location of Jalan Binuang, Ngarai Sianok,Agam Regency, West Sumatra using a centralized system where the PLTS is positioned at one point while the lighting is combined or united on one pole. The following is the design of the PJU-TS road so that it works and carries out its functions well and as expected and the installation steps are based on procedures and the sun is the only source of energy for the PJU TS.Keywords:Centralized System PJU-TS Planning for Binuang Road, Ngarai Sianok,Agam Regency, West Sumatra.